JEJAK PERADABAN ISLAM DI SITUS DOROBATA, KABUPATEN DOMPU, NUSA TENGGARA BARAT - I Wayan Sumerata (Balai Arkeologi Bali, 2014)
The process of Islamisation in Dompu was started since the collapse of Majapahit Kingdom. Archaeological data showed that traders coming from the Kingdom of Gowa, Makassar had spread Islam through trade channels. Evidences of the spread of Islam in Dompu can be seen from the ancient tombs, scattered in the region of West Nusa Tenggara. Those tombs are very important artefacts in order to know the process and the influence of Islam in the early spread. Some of the artifacts refering to the influence of Islam are found in Dorobata Site. The data were collected through excavation method, survey, and interviews with descriptive-qualitative analysis, supported by morphological and comparative analysis. The finds of this research are gravestones and sepulcher which is the evidence of burial in Dorobata. The decoration of the gravestone influenced by Bugis-Makassar culture, combined with the previous culture. Proses Islamisasi di Dompu dimulai sejak keruntuhan Kerajaan Majapahit. Data arkeologi menunjukan para pedagang yang berasal dari Kerajaan Gowa, Makassar telah menyebarkan Islam melalui jalur perdagangan. Bukti-bukti penyebaran Islam di Dompu dapat dilihat dari makam-makam kuno yang tersebar di wilayah Nusa Tenggara Barat. Makam ini menjadi artefak yang sangat penting untuk mengetahui proses dan pengaruh Islam pada masa awal penyebarannya. Beberapa artefak yang merujuk ke arah itu ditemukan di Situs Dorobata. Pengumpulan data menggunakan metode ekskavasi, survei, dan wawancara dengan analisis deskriptif-kualitatif, serta ditunjang dengan analisis morfologi dan komparatif. Artefak yang ditemukan adalah nisan dan jirat kubur yang merupakan bukti adanya penguburan di Dorobata. Ragam hias nisan ini dipengaruhi budaya Bugis Makassar yang dipadukan dengan budaya sebelumnya.